THE CULTURAL CONFLICT OF THE AMERICAN INDIAN PEOPLE: A BRIEF OVERVIEW ON TWO AMERICAN INDIAN FICTIONS - Rahmad Hidayat; Rizky Februansyah (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
Indian people are indigenous people of America, who had lived for centuries and long before the coming of European people to America in 15003. There are many tribes, even more than a hundred, among the Indian people. Each of them lived in group and has their own characteristics, such as language, custom, and culture. The contact between the Indian people and the European people brought a new era especially for the Indian people, which later changed the life of the Indian people from traditional into modem. It bears a cultural conflict for Indian people as can be seen in the works of Indian fictions such as House Made of Dawn and Auntie Angie's Cheyenne Affair, both written by Indian people, N Scoll Momaday and Adrian C Louis, respectively. In all cases, both novels represent the problems of cultural conflict encountered by the Indian people when they lived between two cultures, traditional and modem ones. This emerges in the writers' portrayals of their Indian young generation characters as the result of the changing from traditional to modem life.